CONSUMER PROTECTION AS IMPLEMENTATION INSTRUMENT ISLAMIC BUSINESS ETHICS - Rimanto Rimanto; Muhamad Rudi Wijaya; Kholid Hidayatullah (Pascasarjana IAIN Metro, 2021)
Changes in the pattern of trade transactions from conventional patterns to digital patterns, are caused by the development and progress of science and information technology, which in turn brings human users of these technologies to the virtual world, a new life order, there is no physical contact, but can communicate with each other and transact. As with the world of commerce, it does not escape the influence of the digitalization of transactions. Transaction digitization is an option because it affects time and cost efficiency on the one hand, on the other hand due to external factors that make physical contact with each other impossible, such as in the current Covid-19 pandemic, triggering the increasingly massive use of e-commerce as a transaction model. safe in terms of exposure to the virus, However, it is not certain that its safety for consumer protection can be ascertained. The right of consumers to obtain commodities in accordance with the agreement is often neglected, there are some untrustworthy and honest online sellers in carrying out their business activities. This research, using a legal study approach. The method used in writing this journal is a type of empirical legal research using the object of study of normative legal provisions (laws) with their implementation in every legal event that occurs in the community so that this research covers gaps in theory and practice in society, using a fact approach. (The Fact Approach) The Law on the Protection of Consumer Rights Number 8 of 1999 guarantees the fulfillment of consumer rights in a professional manner, by regulating the rights and obligations of the parties bound by the sale and purchase agreement, as well as regulating sanctions if the rights and obligations are not fulfilled. However, what occasionally happens is that the consumer's rights are not fully fulfilled, such as the absence of conformity of commodities with the contents of the agreement. Islam as a universal teaching, perfect values ​​and rules, provides guidelines so that consumers get protection, with the concept and value of transactions based on filar shidiq, amanah, fathanah and tabligh. Lack of guidance from the value system of the philosophy of commerce results in corrupt attitudes/behaviors that occur among producers and sellers, this can be avoided if business ethics based on Islamic business ethics can be understood and used as guidelines for electronic/digital transactions.